Strategic formulations for coping with school evasion: the case of a Higher Education Institution in Ceará - Bizarria, Fabiana Pinto de Almeida (2017)
The study analyzes the strategic formulations of avoidance coping in courses at the National Training Program in Public Administration (PNAP) offered in a distance tertiary institution of Ceará. We used the case study, supported in data from eight semi-structured interviews and documentary queries. Considered the context, process and content strategies based on the analysis of organizational change from 2010 to 2013. Processing of data in Atlas.ti software led to the elaboration of categories. It is pointed out that the avoidance coping aligns with increased credibility in the operation of DE and becomes institutional goal.